The Influence of Employee Welfare and Workplace Facilities on Employee Job Satisfaction - Tasya Safira Firrentin; Komarun Zaman; Nur Hidayah (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the influence of employee well-being and workplace facilities on job satisfaction, focusing on how both factors contribute to employee sense of fulfilment at work. Methodology/approach: Conducted at PT Hutomo Baut Indonesia using a quantitative approach. Data were collected via structured questionnaires and analyzed using SPPS 27 Software, focusing on the variables of employee well-being, work facilities and job satisfaction. The population of 24 employee selected through total sampling. Results/findings: Both employee well-being and workplace facilities have a significant positive effect on job satisfaction. Well-being enhances motivation and initiative, while adequate facilities reduce stress and improve performance. Conclusions: This study shows that employee well-being and workplace facilities significantly influence job satisfaction. Well-being increases motivation and engagement while adequate facilities reduce stress and improve performance, creating a more fulfilling work environment. Together, these factors enhance employees’ sense of fulfilment at work. These findings suggest organizations integrate both factors in HR policies. Limitations: This study limited to two independent variables- employee well-being and workplace facilities, excluding other influential factors such as leadership style, organizational culture or carrier development. The quantitative design also limits deeper exploration of employees’ personal perceptions and experience. Contribution: This study offers valuable recommendations for PT Hutomo Baut Indonesia and similar organizations to develop more employee-focused and sustainable HR policies.